Caring Behavior of Nurses in Pediatric Patients During Hospitalization - Qurrotul Aeni; Ema Darojatul Ulya; Dwi Haryanti (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Caring is the care of the nurse with all his heart towards the patient. Concern, empathy, gentle communication and compassion for the patient will form a therapeutic nurse-client relationship, thus caring for nurses will make patients feel comfortable, safe and feeling less stressed due to the illness they suffer. Objective: The purpose of this study was to describe the caring behavior of nurses in pediatric patients during hospitalization. Method: This study used a descriptive method, the number of samples in this study were 70 parents of pediatric patients who were treated at Dr. H. Soewondo Kendal selected using a purposive sampling technique. The instrument used is in the form of a questionnairecaring behavior. Data was analyzed using descriptive analysis. Results: The results showed that (54.3%) respondents thought that nurses' caring behavior was in a sufficient category, with sub variable details: knowing behavior (55.7%), being with behavior (45.7%), doing behavior for (88.6%), enabling nurses' caring behavior (50.0%), and belief behavior (74, 3%). Conclusions: of the research conducted on respondents in the Dahlai RSUD DR. H. SOEWONDO KENDAL shows that most of the nurses caring behavior is in the sufficient category 38 respondents (54,3%).